Myanmar in Asean : Myanmar-Asean cooperation for development. - Hnin Hnin Aye. (2008)
The main objective of this study is to examine how membership in a regional organization benefit underdeveloped country like Myanmar. This dissertation argues that Myanmar join ASEAN with the hope that interdependence and cooperation among the member countries in the region would bring about development in Myanmar.